(untitled) - Ondrus, Jan; Dicova, Jana (Doprava a spoje, 2010)
The most of transport companies realize the importance of differentiating their products and services from the competition. Trade-mark provides demand on such designation. Its owner obtains a right to prevent anyone using the designation which would be identical or similar with trade-mark. This article deals with significance of trade-mark for transport company